Chiral separation of diastereomers of the cyclic nonapeptides vasopressin and desmopressin by uniform field ion mobility mass spectrometry. Issue 68 (31st July 2018) - Phillips, Shawn T.; Dodds, James N.; Ellis, Berkley M.; May, Jody C.; McLean, John A.
Abstract : In this study ion mobility-mass spectrometry (IM-MS) is used to distinguish chiral diastereomers of the nonapeptides desmopressin and vasopressin. Abstract : In this study ion mobility-mass spectrometry (IM-MS) is used to distinguish chiral diastereomers of the nonapeptides desmopressin and vasopressin. The differences in gas phase cross sectional area ( ca. 2%) were sufficient to directly resolve the enantiomers present in a binary mixture. Results from computational modeling indicate that chiral recognition by IM-MS for nonapeptides is possible due to their diastereomer-specific conformations adopted in the gas-phase, namely a compact ring-tail conformer specific to thel -diastereomer forms.